Política externa e política de defesa: a participação do Brasil na força interna das Nações Unidas no Líbano - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present research has as goal to analyze the importance of Brazilian performance in the United Nations Interim Force in Lebanon (UNIFIL) to the foreign and defense policy of Brazil. Founded in 1945, the United Nations Organization emerged with similar principles as the ones proposed by Brazil’s foreign and defense policy, reinforcing Brazil’s relevance in this organization and the values spread by it. In the field of peace operations, these values are no different since its principles are based on consent, impartiality and the non-use of force with the exceptions of self-defense and mandate’s defense. By the end of 2010, Brazil was invited to control the Maritime Task Force (MTF) in Lebanon due to the European’s voluntary exit. Therefore, the performance of Brazilian forces in UNIFIL showed to be important to the foreign policy since it has lifted the country to a new level concerning the peace scenario and international security, causing the historical and cultural bond with Lebanon to strength. When it comes to political defense, the Armed Forces had their skills developed since they were given real combat experiences. It also draws attention to the fact that the Brazilian’s acting is present in the structural documents of national defense (PND, END, LBDN) affirming its importance. Therefore, the interests of foreign and defense policy’s instances are highlighted – the first, projecting the country as a relevant international actor, and the second, expanding their own national defense capacity.
Foreign policy and defense policy: Brazil's participation in the United Nations' internal force in Lebanon
Keywords: Política de Defesa Brasileira; Política Externa Brasileira; UNIFIL; Brazilian Defense Policy; Brazilian Foreign Policy; UNIFIL; CNPQ::CIENCIAS SOCIAIS APLICADAS